Expert insights into future trajectories: assessing cost reductions and scalability of carbon dioxide removal technologies - Abegg, Manon; Clulow, Zeynep; Nava, Lucrezia; Reiner, David M. (Frontiers in Climate, 2024)
To achieve net-zero targets, it is essential to evaluate and model the costs and scalability of emerging carbon dioxide removal technologies like direct air capture with CO2 storage (DACCS) and bioenergy with carbon capture and storage (BECCS). Yet such efforts are often impeded by varying assessments of the climate impact and potential contributions of these technologies. This study explores the future costs and scalability of DACCS and BECCS to advance net-zero goals. We analyze expert opinions on these technologies' potential costs and deployment scales for 2030, 2040, and 2050. Data was collected from 34 experts, comprising 21 DACCS and 13 BECCS specialists. They provided 90% confidence interval estimates and 'best estimates' for future costs and deployment under two International Energy Agency (IEA) policy scenarios -Stated Policies (STEPS) and Net Zero Emissions by 2050 (NZE). We find that BECCS costs start at a lower level but decrease more slowly, whereas DACCS costs decline more steeply from a higher initial cost. However, DACCS estimates varied significantly among experts, showing no convergence over time. Regarding potential scalability, both technologies are associated with substantially higher deployment under the NZE scenario. Yet the combined estimated capacity of DACCS and BECCS by 2050 is only about a quarter of the CO2 removals projected by the IEA for its NZE scenario (1.9 GtCO2).